Effect of wheat infection timing on Fusarium head blight causal agents and secondary metabolites in grain - Beccari, G.; Arellano, C.; Covarelli, Lorenzo; Tini, F.; Sulyok, M.; Cowger, C. (Elsevier, 2019)
© 2018 Fusarium head blight (FHB) results in yield loss and damaging contamination of cereal grains and can be caused by several Fusarium species. The objective of the present study was to determine, in a greenhouse experiment on winter wheat, how FHB was affected by timing of infection (0, 3, 6 or 9 days after anthesis, daa) by the aggressive species Fusarium graminearum compared to the relatively weak species Fusarium avenaceum, Fusarium poae and Fusarium acuminatum. Measures of FHB development were: symptoms in spikes (visually assessed), fungal biomass (quantified by real time quantitative PCR) and accumulation of fungal secondary metabolites (quantified by liquid chromatography-tandem mass spectrometry) in kernels. With regard to symptoms, F. graminearum was unaffected by inoculation timing, while the weaker pathogens caused greater disease severity at later timings. In contrast, the accumulation of F. graminearum biomass was strongly affected by inoculation timing (3 daa = 6 daa = 0 daa = 9 daa), while colonization by the weaker pathogens was less influenced. Similarly, F. graminearum secondary metabolite accumulation was affected by inoculation timing (3 daa = 6 daa = 0 daa = 9 daa), while that of the weaker species was less affected. However, secondary metabolites produced by these weaker species tended to be higher from intermediate-late inoculations (6 daa). Overall, infection timing appeared to play a role particularly in F. graminearum colonization and secondary metabolite accumulation. However, secondary metabolites of weaker Fusarium species may be relatively more abundant when environmental conditions promote spore dispersal later in anthesis, while secondary metabolites produced by F. graminearum are relatively favored by earlier conducive conditions.